Central and Commercial Bank Balance Sheet Risk Before, During, and After the Global Financial Crisis - Crowley, Joseph (Washington, D.C. : International Monetary Fund, 2015)
This paper presents an overview of exposures in the balance sheets of central banks, banks, and other depository institutions during the past decade, with emphasis on asset growth and currency composition. It exploits the IMF's SRF-based monetary data to show: (i) there was a widely observed buildup of assets prior to the global financial crisis, but there has been no significant reduction in its wake; (ii) the foreign currency composition of the balance sheets of banks and other depository institutions remained remarkably constant in spite of the crisis, significant changes in the composition of balance sheets, and globalization, and does not seem to have been significantly influenced by the behavior of exchange rates; and (iii) exposure to households increased prior to the crisis, but this increased risk was offset by increased capitalization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet